Determinar la estructura horizontal de las especies comerciales del bosque de colina baja de la Comunidad Nativa Nueva Esperanza del Mirin, Distrito del Yavarí - Loreto Perú. 2023 - Solano Bocanegra, Jeferson (2024)
In the study carried out, low hill forest of the native community “Nueva Esperanza del Mirín, Yavarí District - Loreto Peru. Its floristic composition was a total of 1694 trees, 21 commercial forest species and 12 botanical families, where the Myristicaceae and Fabaceae families contain the largest number of species (five species), followed by the Lauraceae family (three species), Meliaceae (two species) and Simaroubaceae, Malvaceae, Moraceae, Lecythidaceae, Sapotaceae, Caryocaraceae, Bignoniaceae, Calophyllaceae (One species each). The volume of individuals by species and diameter class/Ha was 3,618 m3/Ha in the low hill forest of the Nueva Esperanza native community of Mirín in a total of 2641,785 Ha. The Lupuna species (0.526 m3/Ha), Cumala Blanca (0.402 m3/Ha), report the highest volume; On the contrary, Moena (0.006 m3/Ha) and yellow Moena (0.006 m3/Ha) show lower volume. The results indicate that the total timber volume of the 21 species registered in the forest census contains a total volume of 9557.647 m3 for the entire area (2641.785 Ha). Lupuna (1389,379 m3), Cumala blanca (1062,743 m3), contain the highest volume values; On the contrary, Moena, (17,154 m3) and Moena yellow (15,277 m3) have a lower volume. IV. The species Cumala blanca (33.28%), Aguanillo (32.68%), Lupuna (25.94%), Cedro (24.16%) and Cumala (23.95%) are the most ecologically important in the forest of low hill of the native community Nueva Esperanza del Mirín that makes up a total of 140.01% of participation in the structure of this forest. Furthermore, it can be stated that six species report little participation with less than 06% of IVI, which are represented by Machimango (2.29%), Tahuari (2.10%), Lagarto Caspi (1.95%), Moena (1.25%) and Moena yellow (0.78%), which together add up to 8.37% respectively.